Selection of Pseudomonas aeruginosa for biosurfactant production and studies of its antimicrobial activity - H.S. El-Sheshtawy; M.M. Doheim (Egyptian Journal of Petroleum)
Biosurfactants are generally microbial metabolites with the typical amphiphilic structure of a surfactant. This study investigated potential biosurfactants production of Pseudomonas aeruginosa ATCC-10145 and Bacillus subtilis NCTC-1040 using glucose and n-hexadecane as substrates separately and compared it with the production in conventional medium. Pseudomonas aeruginosa growing in BHMS (Bushnell hass mineral salt) medium with glucose as substrate decreased the surface tension from 72 of distilled water to 32 mN/m, this strain had higher reduction than Bacillus subtilis among all the substrates tested. The selection of Pseudomonas aeruginosa for the separation of biosurfactant was determined. The crude biosurfactant was extracted from the supernatant and the yield of the crude biosurfactant was about 1 g/l. Some surface properties of rhamnolipids biosurfactant were evaluated. It also showed antimicrobial activity against different bacteria and fungi strains. The crude biosurfactant showed good action as antimicrobial activity against different bacterial and fungal species.